Making families through adoption - Riley, Nancy; Van Vleet, Krista E. (Contemporary family perspectives, 2012)
This volume examines adoption as a way of understanding the practices and ideology of kinship and family more generally. It focuses primarily on adoption practices in the US but will also use examples of adoption and fostering across cultures to put those American adoption practices into a comparative context.